1963
DOI: 10.1136/bmj.2.5360.783
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Effects of Occlusion of Abdominal Aorta During Nitorgen Mustard Therapy

Abstract: HYPERTENSIONBRITISH 783 MEDICAL JOURNAL in which the blood-pressure should be lowered to improve prognosis (Turner, 1962; Smirk, 1962 Nine patients preferred reserpine with hydrochlorothiazide, three methyldopa with hydrochlorothiazide, and five had no preference. All felt much better on placebo. Neither combination is ideal treatment for symptomless patients who require hypotensive drugs.We are grateful to Mrs. J. Johnstone and Miss J. Fairburn, technicians at the hypertension clinic, who took the bloodpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1964
1964
1975
1975

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…of mercury. Femoral arterial studies have shown that at this pressure arterial occlusion is complete (Harries, Beecher, Brown and Oettgen, 1963). During the past 3 years 312 occlusions have been applied to 94 patients.…”
Section: Figmentioning
confidence: 99%
“…of mercury. Femoral arterial studies have shown that at this pressure arterial occlusion is complete (Harries, Beecher, Brown and Oettgen, 1963). During the past 3 years 312 occlusions have been applied to 94 patients.…”
Section: Figmentioning
confidence: 99%
“…Later the release of histamine like substances in the compressed gut and occluded lower limbs may produce a condition akin to " tourniquet shock ". Harries et al (1963) have shown that a fall in cardiac output and a rise in pulmonary arterial pressure occurs during occlusion. This indicates that an increase in pulmonary peripheral resistance occurs, which may be due to compression of the pulmonary vessels and a reduction in the venous return to the heart.…”
Section: Effects Of Post Occlusion Hypotensionmentioning
confidence: 99%
“…Harries, Beecher, Brown and Oettgen (1963) have examined the haemodynamic effects of this procedure and suggested that post occlusion hypotension may be initially due to an overall decrease in peripheral resistance, due to a sudden increase in the vascular bed when the Kidde tourniquet was released. Later the release of histamine like substances in the compressed gut and occluded lower limbs may produce a condition akin to " tourniquet shock ".…”
Section: Effects Of Post Occlusion Hypotensionmentioning
confidence: 99%